The Fungal Gut Microbiome Exhibits Reduced Diversity and Increased Relative Abundance of Ascomycota in Severe COVID-19 Illness and Distinct Interconnected Communities in SARS-CoV-2 Positive Patients - Reinold, Johanna; Farahpour, Farnoush; Schoerding, Ann-Kathrin; Fehring, Christian; Dolff, Sebastian; Konik, Margarethe; Korth, Johannes; van Baal, Lukas; Buer, Jan; Witzke, Oliver; Westendorf, Astrid M.; Kehrmann, Jan (Frontiers in Cellular and Infection Microbiology, 2022)
Clinical and experimental studies indicate that the bacterial and fungal gut microbiota modulates immune responses in distant organs including the lungs. Immune dysregulation is associated with severe SARS-CoV-2 infection, and several groups have observed gut bacterial dysbiosis in SARS-CoV-2 infected patients, while the fungal gut microbiota remains poorly defined in these patients. We analyzed the fungal gut microbiome from rectal swabs taken prior to anti-infective treatment in 30 SARS-CoV-2 positive (21 non-severe COVID-19 and 9 developing severe/critical COVID-19 patients) and 23 SARS-CoV-2 negative patients by ITS2-sequencing. Pronounced but distinct interconnected fungal communities distinguished SARS-CoV-2 positive and negative patients. Fungal gut microbiota in severe/critical COVID-19 illness was characterized by a reduced diversity, richness and evenness and by an increase of the relative abundance of the Ascomycota phylum compared with non-severe COVID-19 illness. A dominance of a single fungal species with a relative abundance of >75% was a frequent feature in severe/critical COVID-19. The dominating fungal species were highly variable between patients even within the groups. Several fungal taxa were depleted in patients with severe/critical COVID-19.The distinct compositional changes of the fungal gut microbiome in SARS-CoV-2 infection, especially in severe COVID-19 illness, illuminate the necessity of a broader approach to investigate whether the differences in the fungal gut microbiome are consequences of SARS-CoV-2 infection or a predisposing factor for critical illness.